Proceedings of the 14th International Seminar on Paste and Thickened Tailings 2011
DOI: 10.36487/acg_rep/1104_29_simms
|View full text |Cite
|
Sign up to set email alerts
|

Beaching angles and evolution of stack geomoetry for thickened tailings - a review

Abstract: The reliable prediction or management of beach slope and stack geometry is integral to realisation of the potential benefits of thickened tailings technology. Stack geometry not only controls the storage capacity for a given footprint, but also strongly influences post-deposition geotechnical and geoenvironmental performance. Unfortunately, accurate prediction in design has proved difficult. However, there has been significant improvement in understanding the behaviour of tailings after they exit the pipe, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…A comprehensive review and comparison of the methods of beach slope prediction and control of stack evolution was presented in a paper by Simms et al (2011), to which should be added the work presented independently by Li (2011) at the same forum. These papers presented the current status of different ongoing efforts over the past decade and longer by four groups of researchers and practitioners who have to some extent at least published on this topic in recent years.…”
Section: Beach Slope Prediction Methodsmentioning
confidence: 99%
“…A comprehensive review and comparison of the methods of beach slope prediction and control of stack evolution was presented in a paper by Simms et al (2011), to which should be added the work presented independently by Li (2011) at the same forum. These papers presented the current status of different ongoing efforts over the past decade and longer by four groups of researchers and practitioners who have to some extent at least published on this topic in recent years.…”
Section: Beach Slope Prediction Methodsmentioning
confidence: 99%
“…In that same work Fitton (2007) presented three new beach slope models, all of which predicted a range of relevant beach slope data quite well, and certainly more accurately than any of those tested at that time. Simms et al (2011) carried out a predictive test of three models from the literature; Fitton (2007), a modified form of the McPhail (1994) model;and the Simms (2007) model. It was found that the Simms (2007) model was not applicable for predicting full-scale tailings beaches, but was instead suited to predicting initial run-out of slurry in an expanding blob, as well as the local sheet flow of tailings slurry that occurs in small areas on a mature tailings beach.…”
Section: 7mentioning
confidence: 99%
“… A tailings stack growth model based on sound principles. Of the three main models used to predict beach slope (Simms et al, 2011) none is strongly grounded in theory as they are based on Newtonian fluid assumptions. Consequently, they lack the ability to be readily adapted to new slurry and process conditions without extensive large scale testing due to the non-Newtonian behaviour of thickened tailings.…”
Section: A Process Strategymentioning
confidence: 99%